Efforts to Encourage Interest in Covid-19 Vaccination to the Community of Rw 01 Cibodas Baru Village, Tangerang City - Belardo Prasetya Mega Jaya; Annida Dwi Agustin; Fikry Nurhayadi; Rafdi Altaf; Muhammad Hasyim Abdullah; Aulia Rusdiana; Muhammad Ridwan; Muhayaroh Muhayaroh (EQUATOR SINAR AKADEMIA, 2022)
Indonesia is one of countries that has the highest rate of spread of Covid-19 in Asia. The vaccination is one of the Indonesian government's efforts to fight the Covid-19 pandemic. The lack of public knowledge about the Covid-19 vaccine is become the one of obstacle. In the Thematic Student Work Lecture of Sultan Ageng Tirtayasa University in 2021, group 96 held a vaccination socialization program in the form of a webinar. The purpose is to increase the interest of the community in RW 01 Cibodas Baru Village, Tangerang City to participate in Covid-19 vaccination. The method used is a quantitative research using a questionnaire and displaying a comparison of vaccination participants. Based on the results the outreach to the community experienced an increase in interest in participating in vaccination. This can be seen from percentage of people who participated in the Covid-19 vaccination activity in July-August 2021, which was 91.97%.